2016
DOI: 10.1021/acs.macromol.5b02489
|View full text |Cite
|
Sign up to set email alerts
|

Fragility-Confinement Effects: Apparent Universality as a Function of Scaled Thickness in Films of Freely Deposited, Linear Polymer and Its Absence in Densely Grafted Brushes

Abstract: Ellipsometry measurements as a function of cooling rate are used to study nanoscale confinement effects on dynamic fragility (kinetic fragility), m, in supported films of freely deposited, linear polymer. Polymers include neat polystyrene (PS), neat polycarbonate (PC), and PS + 2 wt % 1,10-bis(1-pyrene)decane (BPD) as small-molecule diluent; in each case, the substrate/polymer interface lacks significant attractive interactions. In terms of both the length scale at which confinement effects become evident and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

13
118
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 46 publications
(131 citation statements)
references
References 99 publications
13
118
0
Order By: Relevance
“…At these temperatures, the diffusion of a small molecule through rubbery polymer is so fast that its concentration would easily equilibrate across the total sample thickness of ≈1 µm. These results containing the unwashed PB samples highlights what others have noted [54][55][56][57] that it is important to ensure the quality and purity of the materials studied. Our previous studies [9,10] were done with high quality polymer standards or polymers that we polymerized and washed ourselves such that these issues were not a concern.…”
Section: Resultssupporting
confidence: 67%
See 1 more Smart Citation
“…At these temperatures, the diffusion of a small molecule through rubbery polymer is so fast that its concentration would easily equilibrate across the total sample thickness of ≈1 µm. These results containing the unwashed PB samples highlights what others have noted [54][55][56][57] that it is important to ensure the quality and purity of the materials studied. Our previous studies [9,10] were done with high quality polymer standards or polymers that we polymerized and washed ourselves such that these issues were not a concern.…”
Section: Resultssupporting
confidence: 67%
“…Rubber toughening strategies typically cannot be explained by simple rules of mixtures suggesting local property changes may play an important role. However, one of the challenges with working with commercial polymers is that undisclosed additives may be present in the polymer that affects the observed results . We found a small molecule additive to be present in the PB sample that was observed to migrate to the PS domain and cause plasticization.…”
Section: Discussionmentioning
confidence: 85%
“…[16][17][18][19][20][21][22] However, the different magnitude of changes observed in various PNCs has raised questions about the universality of the underlying mechanism of the adsorption process as the crucial process, and may suggest it to be system-specific rather than a multi-scale characteristic. 23 Nevertheless, based on the current experimental data and theoretical predictions it is possible to specify the criteria that may be responsible for the dynamic changes at the interfaces in nanostructured materials: (1) the fragility of the polymer, 24,25 (2) the interaction strength, 2,4,12 (3) or the softness of confinement. 15 Some of these criteria are well-studied experimentally while others require additional experimental validation.…”
mentioning
confidence: 99%
“…Jin and Torkelson recently compared the thickness dependence of T g breadth for linear polystyrene‐ co ‐vinylbenzocyclobutene (PS‐VBCB) films before and after cross‐linking, both samples exhibited an increase of T g breadth with decreasing film thickness . A smaller T g breadth in PC films with 635 nm thickness than that with 28 nm thickness is also investigated . Kawana and Jones indicated that the PS thin films has a broadening of T g breadth with decreasing thickness measured by ellipsometry .…”
Section: Resultsmentioning
confidence: 99%
“…In Figure , we also find that all samples exhibit an increase of apparent T g breadth with decreasing confining size, which is in agreement with the former results of Torkelson, indicating an increase of apparent T g breadth with decreasing thickness of thin films. In addition, the T + exhibits a significant increase with decreasing confining size, while the T − exhibits only a slight increase with decreasing confining size.…”
Section: Resultsmentioning
confidence: 99%